Customer Satisfaction of Bima Mobile Application Users is Assessed From Service Quality, Feature Completeness, Ease of Use and Transaction Security - Bachtiar Ali Mahadi; Sudarwati Sudarwati; Sarsono Sarsono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study is to (1) test and analyze the effect of service quality on customer satisfaction of Bima Mobile application users; (2) test and analyze the effect of feature completeness on customer satisfaction of Bima Mobile application users; (3) test and analyze the effect of ease of use on customer satisfaction of Bima Mobile application users; and (4) test and analyze the effect of transaction security on customer satisfaction of Bima Mobile application users. The research object is BPD Jateng Boyolali Branch. The population is all customers using the Bima Mobile application; the sample size is 100 respondents calculated using the Leedy formula; the sampling technique uses accidental sampling. The data collection technique uses a questionnaire. The data analysis technique uses multiple linear regression analysis. The results of this study indicate that (1) Service quality influences customer satisfaction among Bima Mobile users (2) Feature completeness influences customer satisfaction among Bima Mobile users (3) Ease of use influences customer satisfaction among Bima Mobile users (4) Transaction security influences customer satisfaction among Bima Mobile users. Keywords: Service Quality, Feature Completeness, Ease of Use, Transaction Security, Customer Satisfaction